Pembangunan Berwawasan Gender Dalam Pertumbuhan Ekonomi Indonesia Dan Perspektif Maqashid Syariah Jasser Auda - Nainggolan, Basaria; Soleman, Riky (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2022)
This study aimed to show the effect of gender-oriented development on Indonesia’s economic growth and the role of gender-oriented development from the perspective of Jasser Auda’s sharia maqashid. This research is a quantitative study using combined panel data analysis from cross-sections of 34 provinces in Indonesia with a time series from 2010-2021. The data source uses secondary data in the form of documentation obtained from the Central Bureau of Statistics and the library. The data analysis technique uses panel regression. Testing the model’s specification uses the fixed effect model (FEM) approach with the Eviews analysis tool. The results show that the ratio of the average length of schooling for women and men positively and significantly affects Indonesia’s economic growth. The life expectancy ratio for women and men negatively affects Indonesia’s economic growth. The ratio of expenditure per capita for women and men does not affect Indonesia’s economic growth. Based on Jasser Auda’s sharia maqashid perspective, gender-oriented development is seen as ammah maqashid. Then the welfare practices are evenly distributed, and there is no inequality between women and men. This research can complement existing theories and become a reference source for other researchers studying gender-oriented development, economic growth, and sharia maqashid.